Biliary atresia with hyaline cartilage at the porta hepatis: a novel finding of undetermined significance. Issue 3 (July 2016) - Gupta, Rakesh Kumar; Batra, Vineeta V.; Sengar, Mamta; Sakhuja, Puja; Rooge, Sheetal N.
Abstract : Biliary atresia is an important cause of liver disease and morbidity in infants with unknown etiology. To date, only five cases of biliary atresia with hyaline cartilage at the porta hepatis have been described. We present the case of a 65-day-old male child, with further insight and detailed discussion of this heterotopia of undetermined significance.